ANALYSIS OF FACTORS AFFECTING THE PRODUCTION LEVEL OF VIRGIN COCONUT OIL (VCO) ENTREPRENEURS IN KARANGASEM REGENCY - Ni Komang Elika Wati; Ni Made Tisnawati (Adisam Publisher, 2025)
This study aims to analyze the effect of capital, raw materials, and labor on the production levels of virgin coconut oil (VCO) entrepreneurs in Karangasem Regency. This regency was chosen because it is one of the largest VCO production centers in Bali Province; however, its productivity level has not yet reached its optimal potential. This research adopts a quantitative approach with an associative causal design using a semi-log regression analysis method to examine the relationship between the independent variables (capital, raw materials, and labor) and the dependent variable (production level). Data were collected from 31 VCO entrepreneurs using a census technique, questionnaires, interviews, and secondary data from the local agriculture office. The results show that both capital and raw materials have a significant effect on the production levels of VCO entrepreneurs in Karangasem Regency. Furthermore, capital and raw materials were found to have a positive and significant partial effect, while labor showed a positive but not statistically significant partial effect on production levels.